ANALISIS PROGRAM LITERASI BACA DALAM MENGOPTIMALKAN MINAT MEMBACA SISWA KELAS V SDN 03 BENGKAYANG - Nober Leo Agung; Margaretha Lidya Sumarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the school literacy program in optimizing the reading interest of fifth-grade students at SDN 03 Bengkayang and to identify the supporting and inhibiting factors in its implementation. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews with 15 students and 1 fifth-grade teacher, questionnaires administered to 15 students, and documentation. Data were analyzed through the stages of data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results of the study indicate that the school literacy program is routinely implemented through a 15-minute reading activity before the learning process begins and reading activities in the school literacy library. The implementation of the literacy program was able to optimize students’ reading interest, as evidenced by their increased enthusiasm in participating in reading activities, higher reading frequency, and the development of independent reading habits both at school and at home. Interview and questionnaire results showed that most students responded positively to the literacy program because it helped improve their understanding of learning materials, broadened their knowledge and insights, enriched their vocabulary, and enhanced their communication skills and self-confidence. Supporting factors included teacher support, the availability of a literacy library, diverse reading materials, and a school environment that encouraged reading activities. Meanwhile, inhibiting factors included the low reading interest of some students, limited availability of certain reading materials that matched students’ interests, and the influence of mobile phone use, which led some students to prefer playing rather than reading at home. Based on the findings, it can be concluded that the school literacy program, implemented regularly and continuously, is able to optimize the reading interest of fifth-grade students at SDN 03 Bengkayang through reading habituation and a conducive school environment, thereby fostering a stronger reading culture.